Three essays on corruption in the Middle East and North Africa - Kirsanli, Fatih, author; Vasudevan, Ramaa, advisor; Tavani, Daniele, committee member; Zahran, Sammy, committee member; Dossani, Asad, committee member (Colorado State University. Libraries, 2022)
This dissertation focuses on the corruption phenomenon at the macro level in the Middle East and North Africa (MENA) after the Arab uprisings regarding its impacts on economic growth and income inequality. The first chapter investigates the relationship between corruption and economic growth. The results show that after the Arab Spring, corruption lowers economic growth. After clustering the MENA countries into three categories -- severe, moderate, and light -- according to the magnitude of the Arab protests and their outcomes, the results are obscure due to the low number of observations. Although the results are not significant in sub-sample regressions, they are robust for the entire data set with alternative corruption indexes. Furthermore, the findings verify that the natural resource curse is a valid argument. Lastly, the Chow test confirms that 2011, the year when the Arab protests started, constitutes a structural break. The second chapter examines the impact of corruption on income inequality. The findings concludes that there is no significant relationship between corruption and inequality for the entire data set. Then, the MENA region is categorized into three sub-regions as in the first chapter to test whether results constitute intra-regional heterogeneity. The robust results reveal a negative and significant relationship between the Arab Spring and inequality in severely affected countries. Nevertheless, the results are insignificant for moderately and lightly affected countries. The third chapter analyzes the heterogeneous findings of the previous chapters. In the first part, crony capitalism, democratization of corruption and rentier state models are discussed to explain the political-institutional characterization of severely, moderately and lightly affected countries. In the second part, severely affected countries are further examined on how corruption income inequality nexus rotates in terms of magnitude and sign and still significant after the Arab Spring. The political economy analysis helps to provide country and group-specific policy recommendations.
Keywords: corruption; income inequality; Arab Spring; political economy; economic growth